4′-Methoxyresveratrol Improves Hepatic Insulin Resistance Induced by a High-Fat-Diet via Anti-Oxidative-Stress Activity - Zhang Z; Zhang X; Yang L; Nie Q; Song G (Diabetes, Metabolic Syndrome and Obesity)
Zhimei Zhang,1 Xuemei Zhang,2 Liqun Yang,1 Qian Nie,3 Guangyao Song1 1Department of Endocrinology, Hebei General Hospital, Shijiazhuang, Hebei, 050000, People’s Republic of China; 2Section of Rheumatology and Immunology, Hebei General Hospital, Shijiazhuang, Hebei, 050000, People’s Republic of China; 3Physical Examination Center, Hebei General Hospital, Shijiazhuang, Hebei, 050000, People’s Republic of ChinaCorrespondence: Guangyao Song, Hebei General Hospital, No. 348 West Heping Road, Xinhua Area, Shijiazhuang, Hebei, 050000, People’s Republic of China, Tel +86-13930119808, Email sguangyao2@163.comBackground: Obesity and a high-fat diet (HFD) are key factors contributing to hepatic fat accumulation and type 2 diabetes mellitus (T2DM). Research indicates that oxidative stress induced by HFD mediates hepatic insulin resistance (HIR) through mechanisms such as promoting inflammation and lipid accumulation. Given that 4′-methoxyresveratrol (4-MR) exhibits remarkable anti-inflammatory and antioxidant activities, it is of great research significance to explore whether it can effectively counteract HFD-induced HIR by enhancing antioxidant stress.Purpose: This study aimed to explore the effects of 4MR on liver oxidative damage and insulin sensitivity.Methods: Mice were fed a HFD for 8 weeks, followed by an intraperitoneal glucose tolerance test to assess insulin resistance. The in-vivo experiments were divided into three groups, including the control group, the HFD group, and the HFD + 4MR group. After 6 weeks of 4MR treatment, blood and liver samples were analyzed for biochemical markers, lipid peroxidation, antioxidant capacity, and liver protein levels. Insulin-resistant HepG2 cells were treated with 4MR and evaluated for proliferation and toxicity.Results: 4MR reduced fasting blood glucose and lipid levels, improved insulin sensitivity, and decreased liver malondialdehyde levels, while increasing catalase and antioxidant enzyme activities. In both mice and HepG2 cells, 4MR increased Sirt1, p-FOXO1, and CAT expression levels and decreased FOXO1 expression levels.Conclusion: 4MR alleviated hepatic oxidative stress, enhanced insulin sensitivity, and reduced glucose levels.Keywords: blood glucose, insulin resistanc, anti-oxidative stress, 4′-methoxyresveratrol, hepatic